Folklore as Ethnic Embodiment Bias: Value Analysis on Karo Folklore - Marsellaa, Emma; Putri, Dian Marisha (Budapest International Research and Critics University, 2020)
The existence of folklore as a folklore is assumed to be an entertaining story for children at bedtime. In fact, the folklore contains a lot of structured messages and messages conveyed implicitly. Folklore often reflects the creativity of traditional societies by still adhering to tradition as a manifestation of creativity that lives and is passed down from generation to generation. The study uses the opinion of Dundes (1965: 2) Bruvand (1965), Danandjaja (1997) and the concept of value according to Bascom in Danandjaja (1995: 3-20). Miles and Huberman's (2007) qualitative research methodology includes data collection of folklore texts, data presentation, and drawing conclusions or verification. Based on the analysis of folklore data, 10 folklore folklore were selected which were collected in the book Sukapiring et al. (1993). The results obtained based on the folklore text found ethnic values in folklore texts by interpreting behavioral trends as psychological symptoms based on the data found that the values in the Karo folklore data analyzed were found a) Educational values such as: the value of obedience to parents, the value of patience, b) Moral values found in folklore are the values of humility, forgiveness, and not being arrogant, and c) the religious values found in Karo ethnic folklore, namely: not being greedy, not playing gambling, and trusting. These values can represent the bias of the Karo ethnic community who instill values through folklore.